2021
DOI: 10.3389/fgene.2021.671128
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of a Four-Long Non-coding RNA Signature Associated With Immune Infiltration and Prognosis in Colon Cancer

Abstract: The emerging evidence has demonstrated the critical roles of long non-coding RNAs (lncRNAs) as regulators in the tumor immune microenvironment (TIME). However, the tumor immune infiltration-associated lncRNAs and their clinical significance in colon cancer have not yet been thoroughly investigated. This study performed an integrative analysis of lncRNA expression profiles and immune cell infiltration profiles and identified 258 immune infiltration-associated lncRNAs. Of them, four lncRNAs (AC008494.3, LINC0092… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…However, given that the 5-year survival rate (OS) of CC is relatively high, more and more researches have investigated the influencing factors for CC prognosis. In general, the factors that affect the prognosis of CC mainly come from the tumor aspect, including the size of the tumor, the location of the tumor, and the depth of tumor infiltration ( Feng et al, 2021 ; Huang et al, 2021 ; Wang et al, 2021 ). Of course, distant metastasis also contributed to the reduction in the survival of CC patients ( Chang et al, 2017 ; Nakamura et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, given that the 5-year survival rate (OS) of CC is relatively high, more and more researches have investigated the influencing factors for CC prognosis. In general, the factors that affect the prognosis of CC mainly come from the tumor aspect, including the size of the tumor, the location of the tumor, and the depth of tumor infiltration ( Feng et al, 2021 ; Huang et al, 2021 ; Wang et al, 2021 ). Of course, distant metastasis also contributed to the reduction in the survival of CC patients ( Chang et al, 2017 ; Nakamura et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study found a signature featuring 9-lncRNAs related to pyroptosis (SNHG26, MYOSLID, TMEM147-AS1, CCDC183-AS1, AL354836.1, LINC00174, AC023157.2, AC084125.2, and AL137782.1) and revealed that it has the ability to anticipate the prognosis of people with CC. Wang Y. and Tong H. showed that SNHG26 is closely associated with the tumour, immune microenvironment, CC, and bladder cancer [ 57 , 58 ]. MYOSLID promotes the progression of osteosarcoma through the miR-1286/RAB13 axis [ 59 ], and MYOSLID plays a key role in stomach neoplasm through the miR-29c-3p-mcl-1 axis [ 60 ], but it has not been reported in CC.…”
Section: Discussionmentioning
confidence: 99%
“…This means that some basic experiments (such as rt-qPCR) should be used for practical verification to ensure that the genes of interest had sufficient expression ( Zhu et al, 2021 ). To overcome the shortcomings of the above model, new prognostic models based on the strategy of the relative expression of immune-related gene pairing were proposed, which became a mainstream bioinformatics research method ( Sun et al, 2020 ; Wu et al, 2020 ; Wang Y. et al, 2021 ). In this study, we were inspired by the new strategy and attempted to construct a reasonable model with ir-lncRNA pairs assess the prognostic value of ir-lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The differential expression of these lncRNAs indicates that ir-lncRNAs had played an important role in the radioresistance of ESCC. Second, previous studies have shown that lncRNAs achieve biological functions through a variety of target genes, which may involve immune-related genes ( Wang Y. et al, 2021 ). Therefore, we further explored the differential expression of immune genes, which were not only differentially expressed in esophageal cancer tissues with different response characteristics of radiotherapy, but also correlated with the expression of immune lncRNAs, and thus could be considered as target genes of ir-lncRNAs.…”
Section: Discussionmentioning
confidence: 99%